Young medical doctors' perspectives on professionalism: a qualitative study conducted in public hospitals in Pakistan - Aisha Jalil; Qaisar Khalid Mahmood; Florian Fischer (BMC, 2020)
Abstract Background Professionalism is amongst the major dimensions determining the competence of medical doctors. Poor professionalism affects the overall outcome of healthcare services. This study explores the perspectives of young medical doctors on professionalism in Pakistan. Methods A qualitative study based on in-depth interviews was conducted with 60 young medical doctors, aged less than 40 years, who had studied medicine in Pakistani universities, were Pakistani nationals, and were employed at various hierarchical levels, from house officer to consultant specialist, in public tertiary hospitals in Pakistan. The respondents were identified through a multistage maximum heterogeneity sampling strategy. A semi-structured interview guide was developed based on a previous extensive literature review. Written consent was obtained from the hospitals and study participants. Qualitative thematic analysis was applied to analyse the data. Results The data analysis revealed that rigidity of opinions, unacceptability of contrasting perspectives, false pride, and perceived superiority over other professions and patients were major components of poor medical professionalism. Most of the young doctors believed that there is no need to include professionalism and humanity course modules in the medical curriculum, because topics related to social sciences are deemed irrelevant to medicine and judged to be common sense. The doctors recognised good professionalism in themselves, while reporting unprofessional behaviour demonstrated by their colleagues and paramedics. Other factors contributing to poor medical professionalism included the use of social media applications during duty hours, ridiculing patients, substance use such as smoking cigarettes in the office, referrals of complicated cases to other hospitals, freeing up beds before holidays, lack of cooperation from paramedical staff, and inadequate role models. Conclusions Poor medical professionalism among young doctors needs to be addressed by policymakers. There is a need to revisit the medical curriculum to strengthen professionalism. It is essential to develop the qualities of tolerance, teachability, and acceptance in doctors in order to facilitate interprofessional collaborations and avoid medical errors.